PENGARUH KOMUNIKASI DAN MANAJEMEN HUBUNGAN KARYAWAN TERHADAP KINERJA KARYAWAN PADA PT. BANK PANIN DUBAI SYARIAH CABANG MEDAN - Lubis, Anggia Sari (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2016)
The purpose of this study was to measure the influence of communication and employee relationship management on the performance of employees of PT. Dubai Islamic Bank Panin Medan Branch. This study uses a survey approach, while the nature of this study is the description and type of research is quantitative descriptive. Samples were 30 employees at PT. Dubai Islamic Bank Panin Medan Branch. Methods of data collection in this study using a questionnaire. The questionnaire in this study by providing or spreading a list of questions to respondents, the results of research that has met the test of validity, reliability test and classical assumption is processed to produce the following regression equation, Y = 0.042 X1 + X2 0837 + e.The results of multiple linear regression model to get that second variable is the communication and management of employee relations has a positive influence on employee performance PT. Dubai Islamic Bank Panin Medan Branch. The coefficient of determination (R ²) were obtained at 0.712. This means that 71.2% of employee performance can be explained by communication and employee relationship management, employee performance while 28.8% described other variables besides these two variables. Kata kunci: komunikasi, manajemen hubungan karyawan, kinerja karyawan.